Populism and extremism: The immediate political challenges to Europeanism. Issue 102 (June 2019) - Corbet, Shaen; Larkin, Charles
Abstract: In the midst of the banking and economic crises that evolved most aggressively within the peripheral European states, the European Central Bank proceeded to overcome their rigid approach to monetary policy as the Eurozone edged closer towards economic collapse. The financial crises have now been closely followed by a political crisis inspired by the dramatic influx of illegal immigration. As a result, Europe finds itself at a crossroads inspired by political spectrum shifts to the left and the right, with fear, uncertainty fuelling nationalist revolt across a host of European nations. We briefly consider explanations for the individual political spectral-shifts within the European Union, while outlining the growth of populist movements since the most recent parliamentary elections.